Hydrological inflows and losses from cattle ranching impoundments in dry rangelands of Argentina - Magliano, Patricio Nicolás (2024)
Impoundments of the dry rangelands, Argentina, are recharged solely by infiltration excess overland flow. Two impoundments, one for supplying cattle and the other a control, are studied with their hydrological functioning quantified and modelled using UK developed methods. Despite the additional outflow from cattle, the impoundment for cattle stored water for longer (65-day vs 25-day residence time for cattle and control respectively). This is because of cattle trampling the ground reducing the loss of storage via leakage to 15%, compared with 65% storage loss from leakage for the control.